Potret Kegiatan Dakwah di Kabupaten Solok - Abdullah Khusairi (Universitas Islam Negeri Imam Bonjol Padang, 2015)
This paper is the result of a search in depth in 14 villages in the district of Solok, West Sumatra. Initial research for the purpose of propaganda see a map of the actual problems that exist in the field. Through a qualitative approach, this article would like to provide you the most actual picture of how the portrait of proselytizing villages. Some interviews are necessary to obtain the true reality. Search results for two months, finding forms of preach possessed strength in villages of Solok. The potential for very large preach activities. An important element in the villages still exist, at least, in 14 villages were sampled from villages that exist in Solok. However, an important element in the community in need of a touch of novelty, strengthening and improvement of human resources so that no progress results proselytizing activities. There is the impression of stagnation in the field. The shape of the potential, each tribe has a master in charge of religion in the tribe. While in the village government, the density of indigenous villages, has arm development philosophy as well as philosophy of Minangkabau,